Disaster drill – Myagdi District Hospital - Malla, Dhirendra Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2015)
As per Hospital management strengthening programme guidelines, every hospital has to conduct mock drill twice a year to evaluate their situations. We decided to conduct a Drill in Myagdi District hospital with help of HDC chair and DHO.